Mechanism of Coal-Measure Gas Enrichment under Multi-Factor Coupling: A Case Study of the Eastern Pingdingshan Mining Area - Zhang, Yucui (International Journal of Natural Resources and Environmental Studies, 2026)
This study focuses on the Shanxi Formation coal-measure strata in the eastern Pingdingshan mining area and systematically investigates the mechanisms controlling the occurrence and enrichment of coal-measure gas under the coupling effects of sedimentary and tectonic processes. Based on integrated geological datasets, key sedimentary parameters (e.g., mudstone and sandstone ratios) and structural curvature attributes were quantitatively characterized to evaluate their influence on reservoir properties, gas preservation, and migration pathways. The results indicate pronounced spatial heterogeneity in both mudstone and sandstone distributions. Mudstone-dominated zones exhibit strong sealing capacity, favoring gas preservation, whereas sandstone-enriched intervals tend to enhance gas migration. High structural curvature zones are distributed in bands along fold belts and show a strong correlation with coal seam floor undulation. Moderate tectonic deformation promotes fracture development and improves reservoir permeability, while excessive deformation may degrade sealing conditions. The deformation responses of mudstone and sandstone layers are highly consistent, suggesting vertical coherence of tectonic processes. Overall, the coupling of sedimentary and tectonic factors is identified as the primary mechanism governing coal-measure gas enrichment. These findings provide a robust geological basis for favorable zone prediction and the efficient development of coal-measure gas resources.